Prostate cancer risk factors: a UK population based case-control study centered on chronic diseases, medications, sunlight and diet - Robinson, Fredie (2012)
Background: Prostate cancer risk has been associated with several environmental factors but there is little information to indicate the effects of timing and of lifetime exposures that may add to the risk. This thesis aims to investigate the association of six main areas that may contribute to prostate cancer risk (1) body shape & fat distribution, (2) chronic diseases/conditions (diabetes mellitus, hypertension, ischaemic heart diseases and hypercholesterolemia), (3) statin medications (4) painkillers (NSAIDs and paracetamol), (5) skin & sunlight exposure and (6)diet (isoflavones, selenium, vitamin D & lycopene). The exposures will be investigated at different stages of life for subsequent effects on cumulative prostate cancer risk.